Fundamentals of corporate finance - Ross, Stephen A.; Westerfield, Randolph W.; Jordan, Bradford D. (New York : McGraw-Hill Education, 2019)
Provides students with a framework of theory and application to use well after they complete the course. This title empowers students by continually adapting to deliver precisely what they need, when they need it, and how they need it, so your class time is more engaging and effective.
Includes indexes.
oif 16/12/2019
Loans
Keywords: Corporations--Finance; Business enterprises--Finance